Optimization of Protein Extraction from Spirulina platensis to Generate a Potential Co-Product and a Biofuel Feedstock with Reduced Nitrogen Content - Parimi, Naga Sirisha; Singh, Manjinder; Kastner, James R.; Das, Keshav C.; Forsberg, Lennart S.; Azadi, Parastoo (Frontiers in Energy Research, 2015)
The current work reports protein extraction from Spirulina platensis cyanobacterial biomass in order to simultaneously generate a potential co-product and a biofuel feedstock with reduced nitrogen content. S. platensis cells were subjected to cell disruption by high pressure homogenization and subsequent protein isolation by solubilisation at alkaline pH followed by precipitation at acidic pH. Response surface methodology (RSM) was used to optimize the process parameters - pH, extraction (solubilisation/precipitation) time and biomass concentration for obtaining maximum protein yield. The optimized process conditions were found to be pH 11.38, solubilisation time of 35 min and biomass concentration of 3.6 % (w/w) solids for the solubilisation step, and pH 4.01 and precipitation time of 60 min for the precipitation step. At the optimized conditions, a high protein yield of 60.7 % (w/w) was obtained. The protein isolate (co-product) had a higher protein content (80.6 % (w/w)), lower ash (1.9 % (w/w)) and mineral content and was enriched in essential amino acids, the nutritious γ-lenolenic acid and other high-value unsaturated fatty acids compared to the original biomass. The residual biomass obtained after protein extraction had lower nitrogen content and higher total non-protein content than the original biomass. The loss of about 50 % of the total lipids from this fraction did not impact its composition significantly owing to the low lipid content of S.platensis (8.03 %).